2014
DOI: 10.1088/0004-637x/785/2/151
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Spectroscopy of Blue Supergiants in Metal-Poor Dwarf Galaxy NGC 3109

Abstract: We present a quantitative analysis of the low-resolution (∼4.5Å) spectra of 12 late-B and early-A blue supergiants (BSGs) in the metal-poor dwarf galaxy NGC 3109. A modified method of analysis is presented which does not require use of the Balmer jump as an independent T ef f indicator, as used in previous studies. We determine stellar effective temperatures, gravities, metallicities, reddening, and luminosities, and combine our sample with the early-B type BSGs analyzed by Evans et al. (2007) to derive the di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(75 citation statements)
references
References 83 publications
7
68
0
Order By: Relevance
“…Moreover, the independent works of Garcia et al (2014) and Hosek et al (2014) have found evidence that the Fe abundance in IC 1613 and NGC 3109 may be higher than the 1/7Fe value inferred from oxygen. Since Fe is the main driver of the massloss, this mismatch could explain the strong-wind problem.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, the independent works of Garcia et al (2014) and Hosek et al (2014) have found evidence that the Fe abundance in IC 1613 and NGC 3109 may be higher than the 1/7Fe value inferred from oxygen. Since Fe is the main driver of the massloss, this mismatch could explain the strong-wind problem.…”
Section: Introductionmentioning
confidence: 97%
“…In fact, Sextans A is the Local Group galaxy where the most Fe-poor young stars have been found to date (see Fig. 16, Hosek et al 2014). For this reason, Sextans A offers the unique opportunity to study massive stars in a really metal-poor environment.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, this new method has been successfully applied to galaxies out to a distance of 7 Mpc (Urbaneja et al 2008;U et al 2009;Kudritzki et al 2012Kudritzki et al , 2013Kudritzki et al , 2014Hosek et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…No abundance gradient was found neither in NGC 3109 nor in the supergiants stars analyzed by Evans et al (2007) and Hosek et al (2014 As a result of this work we find that the predicted O, N, and Ne enrichment in PNe should be analyzed more deeply in stellar evolution models. The different models explored here agree in some aspects with the results of observations and disagree in others.…”
Section: )mentioning
confidence: 59%
“…PNe show no gradient either, but this is expected as the central stars modified their original O abundance. A chemical gradient was not found by Evans et al (2007) and Hosek et al (2014) either in their analysis of the chemistry of supergiant stars. Therefore all the material in the bar of the galaxy, which is rotating with a velocity gradient of about 17 km s −1 per kpc, seems well mixed (possibly due to the action of the bar).…”
Section: Is There a Relation Between The Kinematicsmentioning
confidence: 84%